2018
DOI: 10.2503/hortj.okd-r01
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Biosynthesis in Apple Fruit

Abstract: Anthocyanin accumulation is responsible for the red color of the skin and flesh of apple fruits (Malus × domestica Borkh.), and redder fruits are more marketable. Pigmentation in the skin of apple fruit varies among different cultivars and is influenced by environmental factors, including temperature conditions and the level of sunlight irradiation. Because warmer temperatures suppress anthocyanin synthesis in the skin of apple fruit, there are increasing concerns that global warming may be detrimental to frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 59 publications
5
64
0
Order By: Relevance
“…Fruits treated with ethephon presented the highest amount of anthocyanins in relation to all treatments in both cultivars. Studies have shown that the syntheses of anthocyanins and ethylene are closely related; however, it is not yet clear how ethylene signaling stimulates the synthesis of anthocyanins in apple peels (HONDA, MORIYA, 2018); what is known is that it promotes the activity of several enzymes that catalyze the biosynthesis of anthocyanins in fruits (LIU et al, 2012). In the 'Venice' cultivar, fruits treated with KCl did not differ in anthocyanin content from ethephon-treated fruits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruits treated with ethephon presented the highest amount of anthocyanins in relation to all treatments in both cultivars. Studies have shown that the syntheses of anthocyanins and ethylene are closely related; however, it is not yet clear how ethylene signaling stimulates the synthesis of anthocyanins in apple peels (HONDA, MORIYA, 2018); what is known is that it promotes the activity of several enzymes that catalyze the biosynthesis of anthocyanins in fruits (LIU et al, 2012). In the 'Venice' cultivar, fruits treated with KCl did not differ in anthocyanin content from ethephon-treated fruits.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, anthocyanins are expressively synthesized, giving the red color of fruits. Therefore, red and bicolored apples rely on the synthesis of anthocyanins to obtain coloration that provides high quality (HONDA, MORIYA, 2018). Anthocyanin biosynthesis pathway is well understood.…”
Section: Introducionmentioning
confidence: 99%
“…They suggest that the slower advance toward the benchmark blush rate caused by warming during the maturation period will offset the advance in fruit maturity induced by the earlier blooming. Honda and Moriya [11] demonstrated that the temperature during fruit ripening of apple trees is an important factor in anthocyanin synthesis in both apple fruit peel and fruit flesh. They observed that the anthocyanin concentrations in the flesh of mature "Pink Pearl" (normal fruit flesh color, pale pink or red; fruit color, red and orange flush) harvested in 2016 were considerably lower than the typical level, probably because of the high temperatures recorded during the ripening period in that year.…”
Section: Effect Of Temperature On Anthocyanin Synthesismentioning
confidence: 99%
“…The review focuses on anthocyanin in apple fruit peel and its health benefits and the means by which this anthocyanin concentration could be improved by regulating cultivation management and breeding cultivars with high anthocyanin levels. The literature on anthocyanin synthesis in red-fleshed apple fruits is not reviewed here; the details of genetic, environmental, and plant hormonal factors involved in anthocyanin synthesis have been reported by Honda and Moriya [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the anthocyanin content of a type 1 genotype varied by 14% depending on the site of production [10]. In addition, both light and temperature affected anthocyanin biosynthesis in apple, and hence the skin and flesh color; for review see [11,12]. Little is known about the effect of orchard management factors during cultivation on color development in apple flesh.…”
Section: Of 11mentioning
confidence: 99%